A Theoretical Study on Wear Simulation in Metal Forming Processes - Sobis, Tomasz; Engel, Ulf; Geiger, Manfred (Journal of Materials Processing Technology, 1992)
One of the main reasons of tool failure in industrial application of metal forming technologies is wear. Typical for this kind of failure is that it affects not only the costs of the process but also the tolerances of the formed parts. The only way to control these features is to develop methods which allow prediction of wear and which are suited to be used in the design stage in order to optimize the process. Starting with a survey of prediction methods, a new concept for the simulation of wear is presented in this paper. © 1992.
LFT Import::2019-07-15 (486)